Aplikasi manhaj tarjih hadith ahkam oleh Muhammadiyah Indonesia / Mujiburrahman Abdullah - Mujiburrahman, Abdullah (2015)
Muhammadiyah is the largest religious social organization largest in Indonesia which was founded by KH. Ahmad Dahlan in 1912. Through qualitative analysis founded approximately 18 (eighteen) regulation which had been implemented by Muhammadiyah in putting a decision, it covers the debate in istidlal, independent thinking, faith, and application of hadith. At the end of Manhaj Tarjih regulations the Council found a specific explanation method istidlal to a hadith, although it is quite simple. The analysis of Manhaj Tarjih regulations will be evaluated according to the standard of tarjih which was founded by the scholars, such; tarjih from the point of transmission, tarjih texts and terms of hadith and tarjih from other factors. The valuation extend to application in determining the verdict. Have they apply them in determining the verdict or not entirely applied. For this study, two research methodologies will be used, namely the method of data collection and data analysis method. For the former, library research, field study and interview are implemented. To analyze the data, inductive method, deductive, and comparative method are used. On the numerous fatwas issued by Muhammadiyah, researcher founded no 6 (six) fatwas seem to conflict with the existing methods but only limited to the hadith ahkam. Muhammadiyah in resolving legal issues not only take tarjih methods consideration, but also look to the maslahah, place and time. The results of the 6 (six) fatwas above, have discrepancies with tarjih methods, including; hadith that contain imperative meaning, mursal, da'if are more common in use and also hadith that not substantiated by another sunnah.